Rôle des acteurs dans le processus d’élaboration de projets routiers - Shahinaz Sayagh; Agnès Jullien; Anne Ventura (Développement Durable et Territoires)
From preliminary studies to the execution of road works, a road project is submitted to a succession of decisions, following a regulated procedure. This succession of choices is bordered by environmental, technical and financial constraints. Thus, the decisional process is complex, especially because various and numerous actors are implied. In this context, contribution of research can consist in elaborating methods that can inform on potential consequences of successive decisions, in terms of sustainable development. This expects an analysis of decision criteria that are specific to each actor inside the decisional process. The objective of this paper is to analyze on which general stakes the decisional criteria are based. First, factual elements of the decisional process are extracted from regulations. Then, non regulated criteria are investigated through the collection of expressions of different actors. A discussion put the obtained results in the perspective of environmental and consultation stakes. The analysis shows the difficulty to express a list of explicit decisional criteria that respond to the stakes of sustainable development. Environmental stakes are found better considered when a consultation approach is performed at the very beginning of the project. This consultation can only be decided by the client or the project manager, because this goes further than strict regulation demands. However this approach is often limited to local stakes, whereas planetary environmental stakes, such as climate change or natural resources depletion, are often neglected.